ANALISIS KEBERAGAMAAN PEMUDA HIJRAH KOMUNITAS SHIFT PERSPEKTIF EMIK-ETIK - Rika Dilawati; Dadang Darmawan; Wawan Hernawan; Raden Roro Sri Rejeki Waluyojati; Wahyudin Darmalaksana (UIN Sunan Gunung Djati Bandung, 2020)
This study aims to analyze the diversity of Pemuda Hijrah in the Shift community in the Masjid Agung Trans Studio Bandung. This research is a qualitative type through field studies using the emic-ethical approach. The results and discussion of this study include the conceptualization of religiosity, the existence of Pemuda Hijrah the Shift community, and the analysis of the religiosity of Pemuda Hijrah the Shift community at the Masjid Agung Trans Studio Bandung. This study concludes that the religiosity of the Shift community Pemuda Hijrah represents five dimensions of diversity, namely knowledge, beliefs, rituals, experience, and religious commitment. This study recommends further research with a holistic perspective.